2014
DOI: 10.1111/jnc.12662
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR‐206 and other muscle‐specific microRNAs as non‐invasive biomarkers for Duchenne muscular dystrophy

Abstract: Creatine kinase has been utilized as a diagnostic marker for Duchenne muscular dystrophy (DMD), but it correlates less well with the DMD pathological progression. In this study, we hypothesized that muscle-specific microRNAs (miR-1, -133, and -206) in serum may be useful for monitoring the DMD pathological progression, and explored the possibility of these miRNAs as potential non-invasive biomarkers for the disease. By using real-time quantitative reverse transcription-polymerase chain reaction in a randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 40 publications
6
63
1
1
Order By: Relevance
“…By targeting IGF-1 and p85α proteins, miR-29 inhibited muscle protein synthesis and myogenesis since IGF-1 and p85α are well established signaling molecules for protein translation and a decrease in these proteins was observed during muscle atrophy including sarcopenia (Owino et al, 2001; Barbour et al, 2005; Park et al, 2009; Smith et al, 2012). Overexpression of miR-29 in skeletal muscle also resulted in an increase in cell cycle arrest proteins, Cyclin-Dependent kinase inhibitor 2A, (p16Ink4A) and Retinoblastoma protein (pRB) in agreement with the increased expression of these proteins in aged muscle (Hu et al, 2014a,b). Thus, miR-29 regulates the levels of various proteins directly or indirectly eventually resulting in muscle atrophy during aging.…”
Section: Mirnas In Skeletal Muscle Agingmentioning
confidence: 80%
See 2 more Smart Citations
“…By targeting IGF-1 and p85α proteins, miR-29 inhibited muscle protein synthesis and myogenesis since IGF-1 and p85α are well established signaling molecules for protein translation and a decrease in these proteins was observed during muscle atrophy including sarcopenia (Owino et al, 2001; Barbour et al, 2005; Park et al, 2009; Smith et al, 2012). Overexpression of miR-29 in skeletal muscle also resulted in an increase in cell cycle arrest proteins, Cyclin-Dependent kinase inhibitor 2A, (p16Ink4A) and Retinoblastoma protein (pRB) in agreement with the increased expression of these proteins in aged muscle (Hu et al, 2014a,b). Thus, miR-29 regulates the levels of various proteins directly or indirectly eventually resulting in muscle atrophy during aging.…”
Section: Mirnas In Skeletal Muscle Agingmentioning
confidence: 80%
“…Several studies have determined the expression of myomiRs, miR-1, -133, and -206 levels in serum of DMD patients and found that these myomiRs were upregulated. Consistently, miR-206 correlates with DMD pathology and thus could be a useful biomarker for DMD along with creatine kinase (Cacchiarelli et al, 2011; Mizuno et al, 2011; Vignier et al, 2013; Zaharieva et al, 2013; Hu et al, 2014a,b; Roberts et al, 2014). Furthermore, miR-145 and miR-133a were shown to be potential biomarkers in a mouse model of DMD (Endo et al, 2013).…”
Section: Mirnas In Duchenne Muscular Dystrophymentioning
confidence: 90%
See 1 more Smart Citation
“…Likewise, children with DMD present higher blood levels of these miRNAs, which correlate with low muscle strength and function, and with the severity of muscle damage [77]. Especially miR-206 represents a good candidate for detection and progression of DMD [77]. MiR-206 plays a role in skeletal muscle regeneration: following muscle injury, miR-206 is upregulated in satellite cells and may promote muscle regeneration [78].…”
Section: Circulating Mirnas and Exercisementioning
confidence: 98%
“…Serum levels of miR-1, -133a and -206 are increased in murine and canine models of Duchenne muscular dystrophy (DMD) [3]. Likewise, children with DMD present higher blood levels of these miRNAs, which correlate with low muscle strength and function, and with the severity of muscle damage [77]. Especially miR-206 represents a good candidate for detection and progression of DMD [77].…”
Section: Circulating Mirnas and Exercisementioning
confidence: 98%